Журналістика рішень в економічній проблематиці: підходи до реалізації (на матеріалах видання «Forbes Україна») - Страдецька, Олександра Романівна; Stradetska, Oleksandra Romanivna (Ірпінь, 2024)
Магістерське дослідження розглядає динаміку визначення узагальненої моделі журналістики рішень, її ознак, характеристик та підходів до реалізації на матеріалах видання. За результатами дослідження сформульовані особливості механізму запровадження журналістики рішень у вітчизняних масмедіа.

The master's research examines the dynamics of defining the generalized model of decision journalism, its features, characteristics and approaches to implementation on the publication's materials. Based on the results of the research, the peculiarities of the mechanism of introducing decision journalism in the domestic mass media were formulated.
Journalism of decisions in economic issues: approaches to implementation (based on the materials of the publication "Forbes Ukraine")
Keywords: Solution Journalism; журналістика рішень; модель медіа; економічна проблематика; Solution Journalism; decision journalism; media model; economic issues